The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acssuschemeng.2c04995
|View full text |Cite
|
Sign up to set email alerts
|

Y-Doped BaCeO3 Perovskite-Supported Ru Catalysts for COx-Free Hydrogen Production from Ammonia: Effect of Strong Metal–Support Interactions

Abstract: The development of highly efficient Ru-based catalysts for NH3 decomposition is necessary to enable the utilization of NH3 as a CO x -free H2 carrier. Modulation of the interactions between the basic support materials and Ru particles significantly enhances the performance of Ru-based catalysts for NH3 decomposition. In this study, the strong metal–support interaction (SMSI) interface between the BaCeO3 perovskite support and Ru particles was controlled by yttrium (Y) doping in the range of 0–20 mol %. The sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…8 °C and 466.1 °C. Hence, the reduction for the impregnated sample was opted to be at 450 °C for 1 h. The peaks observed at 80-120 °C and 450-500 °C are attributed to the reduction of Ru 4+ to metallic Ru and the support surface oxygen species, respectively [21,22]. Some references imply that the peak at 450-500 °C could be also attributed to the reduction of bulk Ru [23,24].…”
Section: Resultsmentioning
confidence: 99%
“…8 °C and 466.1 °C. Hence, the reduction for the impregnated sample was opted to be at 450 °C for 1 h. The peaks observed at 80-120 °C and 450-500 °C are attributed to the reduction of Ru 4+ to metallic Ru and the support surface oxygen species, respectively [21,22]. Some references imply that the peak at 450-500 °C could be also attributed to the reduction of bulk Ru [23,24].…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, a support with a high specific surface area can enhance the dispersal of Ru nanoparticles, leading to improved NH 3 adsorption capacity [ 92 , 93 , 94 ]. Secondly, the characteristics of the support itself can have a synergistic effect with Ru nanoparticles, thereby enhancing catalytic activity [ 23 , 95 , 96 , 97 , 98 , 99 ]. For example, Jeon et al synthesized a Y-doped BaCeO 3 perovskite and constructed a strong metal support interaction (SMSI) interface with Ru particles, as shown in Figure 13 [ 95 ].…”
Section: Catalysts For Nh 3 Decompositionmentioning
confidence: 99%
“…Yun et al confirmed that modulating the SMSI could efficiently enhance the catalytic properties of Ru/BCY- x catalysts, which provided an efficient way for catalyst modification. 310 Chae et al prepared a series of Ru doped La x Ce 1− x O y composites for NH 3 catalytic decomposition and confirmed that N 2 desorption was the rate-determining step in the reaction 311 To reduce costs, non-noble metal-based catalysts for NH 3 decomposition have been explored. Various strategies have been employed to improve the catalytic activity, such as designing spatially confined metal nitrides, using one-pot cation–anion double hydrolysis synthesis route, and employing a sol–gel method with a second support material.…”
Section: Ammonia and Related Chemicalsmentioning
confidence: 99%